Green Marketing Strategy and Brand Image: The Role of The Big Five Personality Traits in Pangandaran Ecotourism - Rahayu, Isyana; Herdiyanti; Ahmad Supriatna, Dani; Rahman, Farid (Business Review and Case Studies, 2025)
Background: Pangandaran nature tourism, one of the leading destinations in West Java, faces several challenges in maintaining environmental sustainability while providing a positive impression to tourists who are increasingly concerned about sustainability.Purpose: This study aims to analyze the influence of green marketing strategies on brand image through the mediating role of The Big Five Personality Traits in Pangandaran nature tourism.Methodology: This is an explanatory study using a quantitative approach conducted from May to December 2025 in several natural tourist destinations in Pangandaran. Data were collected through Likert questionnaires and structured interviews with 400 respondents aged 19–35 years who were determined using the Slovin formula and an incidental sampling technique. Data analysis used Structural Equation Modeling (SEM) based on Partial Least Squares (PLS).Finding/Result: The results show that green marketing strategies have a significant effect on The Big Five Personality Traits and brand image, and that there is a mediating role of the Big Five personality traits in green marketing strategies and brand image.Conclusion: This study concludes that green marketing strategies play an important role in building the brand image of Pangandaran nature tourism, both directly and through the mediation of The Big Five Personality Traits, so that the consistent application of green marketing practices is key to strengthening the image of a sustainable destination.Originality/Value: The novelty of this study lies in examining the mediating role of the Big Five Personality Traits in the relationship between green marketing strategies and brand image in the context of nature tourism, which has rarely been studied.Keywords: brand image, green marketing, the big five personality traits, tourism, Pangandaran